Analisis Upaya Guru IPS Meningkatkan Minat Membaca Peserta Didik Pada Pembelajaran IPS Kelas VIII SMP Negeri 06 Ngabang - -, Veronika; Aminuyati, Aminuyati; Wiyono, Hadi; Ulfah, Maria; Karolin, Venny (Peneliti.net, 2024)
The research aims to find out how social studies teachers at SMP Negeri 06 Ngabang attempted to increase students' interest in reading, as well as what factors influenced their efforts and what challenges they encountered. This research used a descriptive qualitative method. The information was gathered through observation, interviews, and documentation. In this research, the researcher used both primary (including social eighth-grade instructors, librarians, and eighth-grade students) and secondary data sources. The researcher used interactive data processing techniques that consist of three stages: data reduction, data presentation, and conclusion. The results indicated that: (1) The social studies teacher's efforts to increase eighth-grade students' interest in reading in SMP Negeri 06 Ngabang by providing reading time, selecting reading material, and acting as a motivator, counselor, and evaluator. (2) The teacher's efforts to increase eighth-grade students' interest in reading are influenced by the teacher and students' enthusiasm for reading, supportive infrastructure, and learning environments. (3) The challenge to the teacher's efforts to increase eighth-grade students of SMP Negeri 06 Ngabang's interest in reading is that there was students’ lack of interest in engaging in reading activities, as reported by the teacher